Acute toxicity of the intranasal administration of Anredera cordifolia extract in Wistar Rats - Widuri, Asti; Febriansah, Rifki (Pharmaciana, 2024)
Anredera cordifolia (AC) known as binahong plant in Indonesia is commonly used for traditional medicine since ancients. AC contains of secondary metabolites such as flavonoids that have anti-oxidative, anti-inflammatory, anti-mutagenic and anti-carcinogenic properties. Many flavonoids compound that has anti-inflammatory activity were potential for treatment of nasal inflammatory such as allergic rhinitis. This study aims to evaluate the preclinical safety of acute intranasal administration of AC extract in laboratory wistar rats. Acute toxicity using the intranasal route of administration of AC extract was evaluated on 30 female wistar rats, divided five rats for control, and each five of doses 5%, 10%, 25%, 50% and 75%. Observation during 14 days for the incidence of mortality and signs of toxicity. The AC extract intranasal administration doses at 5%, 10%, 25%, 50% and 75% did not show mortality or treatment related adverse events and did not showed significantly changes on blood profile. The AC extract was found safe until 75% for nasal administration in wistar rats.